Holozäner Klimawandel im Becken der Laguna de Gallocanta (Iberisches Randgebirge).: Die Rekonstruktion vorzeitlicher geomorphologischer Prozeßgefüge mit Hilfe der statistischen Analyse mineralogischer und geochemischer Indikatoren limnischer Sedimente - Schütt, Brigitta; Baumhauer, Roland (ERDKUNDE, 1999)
Core-based paleoenvironmental investigations have been almost dominated by micro-paleontological, mostly pollen-based, studies. Inorganic features of lake sediments were predominantly studies with mineralogical analyses to identify lake typology (depth of water column, lake phase, salinity). In this investigation, geochemical features of lacustrine sediments were investigated to supplement mineralogical information by studying the indicators of weathering and soil forming processes and reconstruction of the overall geomorphological system. A 95 cm core profile of lacustrine sediments from the isolated lake basin of the Laguna de Gallocanta, central Iberian Chain, was the subject of mineralogical and geochemical investigation. The environmental and depositional changes are confirmed by: varying concentrations of SiO2, CaO, P2O5, Fe2O3-MnO-ratio, ECaO,MgO-SiO2-ratio, statistical relationship of silica and phosphate content to metallic oxide content, and the Mg-Ca-ratio of protodolomites, compared with the position of the diffraction angle of the dolomite’s major diffraction peak. The deposition of the underlying strata (section 1) occurred under sub-arid conditions. The environment changed to sub-humid conditions during the late Middle Ages and during the Little Ice Age when the sediments in section 2 were deposited. Increasing aridity influenced the accumulation of the most recent sediments (section 3).